2014
DOI: 10.1186/1756-3305-7-296
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Lymnaea fuscus and Radix balthica to Fasciola hepatica through the experimental infection of several successive snail generations

Abstract: BackgroundHigh prevalence of Fasciola hepatica infection (>70%) was noted during several outbreaks before the 2000s in several French farms where Galba truncatula is lacking. Other lymnaeids such as Lymnaea fuscus, L. glabra and/or Radix balthica are living in meadows around these farms but only juvenile snails can sustain complete larval development of F. hepatica while older snails were resistant. The low prevalence of infection (<20%) and limited cercarial production (<50 cercariae per infected snail) noted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
0
11
0
6
Order By: Relevance
“…Despite the difficulties recorded in experimental infections of Radix spp. with F. hepatica [ 18 ], studies have shown that snails infected at the juvenile stage [ 19 ] or persistently exposed to F. hepatica over successive generations, are more susceptible to infection and eventual shedding [ 20 ]. These results could also explain the F. hepatica -positive P. antipodarum recorded in our study, however, it must be stressed that these infected snails were not dissected, and thus no confirmation of the patency of infection can currently be made.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the difficulties recorded in experimental infections of Radix spp. with F. hepatica [ 18 ], studies have shown that snails infected at the juvenile stage [ 19 ] or persistently exposed to F. hepatica over successive generations, are more susceptible to infection and eventual shedding [ 20 ]. These results could also explain the F. hepatica -positive P. antipodarum recorded in our study, however, it must be stressed that these infected snails were not dissected, and thus no confirmation of the patency of infection can currently be made.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the age resistance of P. columella to C. daubneyi infection, this situation may not be stable over the following years and a change in the susceptibility of these populations to this digenean can be expected if miracidia are permanently present in the habitats where snails are living. An argument supporting this last assumption came from the two reports by Rondelaud et al [ 34 , 35 ]. Pre-adults (4 mm in height at exposure) of three lymnaeid species ( L. fuscus , L. glabra , Radix balthica Linnaeus, 1758 [ 24 ]) are known to be resistant to F. hepatica infection [ 9 , 19 , 28 ].…”
Section: Discussionmentioning
confidence: 86%
“…Pre-adults (4 mm in height at exposure) of three lymnaeid species ( L. fuscus , L. glabra , Radix balthica Linnaeus, 1758 [ 24 ]) are known to be resistant to F. hepatica infection [ 9 , 19 , 28 ]. In contrast, the F. hepatica infection of several successive generations of pre-adults, coming from parents already infected with this parasite, resulted in a progressive increase in prevalence and intensity of snail infection [ 34 , 35 ]. If in the future, P. columella colonizes French hydrographical networks up to open drainage systems, this lymnaeid might play an active role in C. daubneyi transmission and supplant the local common snail host, G. truncatula .…”
Section: Discussionmentioning
confidence: 99%
“…This approach is, however, essential for understanding the development of the parasite life cycle, and thus to evaluate the risk of dispersion and contamination of the parasite in populations of definitive hosts. Our study aims to find these hosts in natura for different species of protostrongylids previously isolated from lungs of hares in France, in order to identify the host-parasite relationship and more precisely the gastropod-nematode relationship, by using techniques previously tested for Trematodes [ 64 - 66 ].…”
Section: Discussionmentioning
confidence: 99%